PEMBENTUKAN KELAS SOCIAL SUPPORT SUAMI TERHADAP KEYAKINAN IBU MENYUSUI ASI EKSKLUSIF UNTUK PENCEGAHAN STUNTING - Juraida Roito Harahap; Siska Helina; Septi Indah Permata Sari (EBIMA : Jurnal Edukasi Bidan di Masyarakat, 2023)
ABSTRACT The paternal figure assumes a crucial role as the primary supporter, possessing the capacity to exert influence over the duration of breastfeeding. Consequently, it is imperative for fathers to actively engage in their role to ensure the successful continuation of breastfeeding. Antenatal education programs have been suggested to enhance fathers' understanding of breastfeeding, despite fathers’ historical lack of involvement in such educational initiatives. Mothers frequently experience concerns regarding a potential decrease in their milk supply and lack confidence in exclusively breastfeeding their infants with breast milk. This activity aims to establish a social support group for husbands aimed at promoting the belief of exclusive breastfeeding among mothers as a means of preventing stunting. Additionally, the study aims to assess the average knowledge level among husbands before and after participating in the social support class. The aforementioned activity was conducted within Kelurahan Harjosari of Pekanbaru City, involving twelve male participants. The community service activities have a duration of 7 months. After a series of eight meetings, it was observed that a social support class for husbands was successfully established in Kelurahan Harjosari, known as the Ideal Husbands Supporting Breastfeeding Group (KSIP-ASI), and notably, attending this social support class significantly improved husbands' knowledge, with an increase of 83.3%. Kelurahan Harjosari is expected to prioritize and support the continuation of KSIP-ASI initiatives, thereby increasing the number of participants and enabling breastfeeding mothers to access comprehensive information on exclusive breastfeeding. Keywords: Class Social Support, husband, breastfeeding.